Pseudoneglect in sentence bisection: a comparison between Italian and Chinese. Issue 5 (3rd July 2016) - Arduino, Lisa S.; Veronelli, Laura; Cai, Lin; Xue, Shuwei; Corbo, Massimo; Zhang, Yaxu
ABSTRACT: Both reading habits and cerebral asymmetries may play a role on bisection bias. There has been shown to be more recruitment of the right hemisphere in reading Chinese, compared to Japanese or alphabetic scripts. One therefore would expect that for sentence bisection in Chinese compared to Italian, a stronger allocation of attention to the left, mediated by the right hemisphere, would yield larger leftward bisection errors. In this study, native Chinese and Italian speakers bisected Chinese and Italian sentences, respectively, which varied in linguistic domain (syntactic or semantic coherence, definiteness and heaviness) and in the position of the linguistic manipulation (left, right and absent). The sentences were bisected more leftwards for Chinese than for Italian. Bisection deviations were further modulated by the position of the linguistic manipulation, though only for Chinese. We concluded that visuo-perceptual, linguistic and attentional factors influence sentence bisection, in a different way in Italian and Chinese.